In-Situ Polarized Neutron Reflectometry Study of the Passive Film Growth on Fe-20Cr Alloy. Issue 11 (27th March 2019) - Ha, Hung M.; Fritzsche, Helmut
Abstract : Metal dissolution and passivation of Fe-20Cr alloy in an alkaline solution were investigated using in-situ polarized neutron reflectometry. The dissolution of the alloy, the thickness of sub-layers in the passive film, the interfacial roughness between layers, and the scattering length density profile of the passive film were measured with sub-nanometer resolution. An anodization ratio for oxide growth of 3.4 ± 0.4 nm/V was determined. The oxide formation efficiency and the layer density at different applied potentials were also quantified.